2004
DOI: 10.1128/ec.3.1.82-90.2004
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Functions That Control Sensitivity to Topoisomerase-Targeting Drugs

Abstract: DNA topoisomerases play critical roles in a wide range of cellular processes by altering DNA topology to facilitate replication, transcription, and chromosome segregation. Topoisomerases alter DNA topology by introducing transient DNA strand breaks that involve a covalent protein DNA intermediate. Many agents have been found to prevent the religation of DNA strand breaks induced by the enzymes, thereby converting the enzymes into DNA-damaging agents. Repair of the DNA damage induced by topoisomerases is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Saccharomyces cerevisiae cells defective in rad52 as well as strains with defects in other recombination repair genes, such as rad50, mre11, and rad54 mutants, are hypersensitive to topoisomerase II poisons (6,7). Similar results have been observed in fission yeast mutants that are defective in DNA repair by homologous recombination (8).…”
Section: Introductionsupporting
confidence: 61%
“…Saccharomyces cerevisiae cells defective in rad52 as well as strains with defects in other recombination repair genes, such as rad50, mre11, and rad54 mutants, are hypersensitive to topoisomerase II poisons (6,7). Similar results have been observed in fission yeast mutants that are defective in DNA repair by homologous recombination (8).…”
Section: Introductionsupporting
confidence: 61%
“…Cell Survival after CPT Treatment HR plays critical roles in suppressing genome instability and promoting cell survival after CPT exposure (Arnaudeau et al, 2001a;Malik and Nitiss, 2004;Sorensen et al, 2005). Thus, the conclusion reached above also suggests that Recql5 functions in a pathway that has a nonoverlapping role with HR with respect to cell survival after CPT treatment.…”
Section: Recql5 Functions Nonredundantly With Rad51 To Promotementioning
confidence: 79%
“…It is currently believed that the DSBs associated with such collapsed replication forks represent the main cytotoxic lesion induced by CPT (Ryan et al, 1991;Shao et al, 1999;Furuta et al, 2003). Consistent with this current hypothesis, it has been shown that homologous recombination repair (HRR) and the signal transduction cascade that is involved in this repair process both play critical roles in suppressing genome instability and promoting cell survival after CPT exposure (Arnaudeau et al, 2001a;Malik and Nitiss, 2004;Sorensen et al, 2005). Therefore, CPT has been widely used to interrogate the mechanisms involved in We recently reported that Recql5-deficient mouse cells were prone to gamma H2AX focus formation and gross chromosomal rearrangements (GCRs) after CPT treatment (Hu et al, 2007).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, TDP2 can act as a backup pathway in the absence of TDP1 (29), and overexpression of TDP2 is sufficient to complement the hypersensitivity of TDP1-deficient budding yeast to camptothecin (CPT) (30). Mre11 has also been shown to cleave 3′-phosphotyrosyl-DNA bonds (31) and repair Top1cc in parallel with TDP1 (32)(33)(34). These results provide strong evidence that gkt encodes TDP1 in Drosophila.…”
Section: Resultsmentioning
confidence: 99%